2018
DOI: 10.4103/psychiatry.indianjpsychiatry_271_14
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in Wives of persons with Alcoholism: An Indian exploration

Abstract: Context:Mental health has currently shifted focus from “deficit” to strength-based approaches such as Resilience. Coping styles and personality factors have been well studied in Wives of persons with Alcoholism (WopA) but not Resilience. Alcohol dependence in spouse is seen as an adversity.Aims:To evaluate Resilience in the WopA and explore its relationship with marital quality and clinical variables of Alcohol Dependence in their husbands.Settings and Design:A cross-sectional study in a tertiary care hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
6
1
Order By: Relevance
“…Our study established a negative correlation between age at onset of dependence and all resilience subscales except for family cohesion and with the resilience total score. A study with spouses of persons with alcohol abuse or dependence, in contrast with our study, found no correlation between age at onset of dependence or age at first consumption of alcohol and spouses' resilience (36). Another study with spouses of alcoholor heroin-dependent individuals also found no significant level of correlation between burden on the caregiver and age at onset (35).…”
Section: Discussioncontrasting
confidence: 99%
“…Our study established a negative correlation between age at onset of dependence and all resilience subscales except for family cohesion and with the resilience total score. A study with spouses of persons with alcohol abuse or dependence, in contrast with our study, found no correlation between age at onset of dependence or age at first consumption of alcohol and spouses' resilience (36). Another study with spouses of alcoholor heroin-dependent individuals also found no significant level of correlation between burden on the caregiver and age at onset (35).…”
Section: Discussioncontrasting
confidence: 99%
“…This insight is vital for shaping interventions, indicating that enhancing these aspects could bolster resilience in families impacted by AUD. The study suggests various strategies to improve the quality of life for wives of individuals with AUD, such as facilitating access to support groups, community engagement programs, and resources for personal growth [ 25 - 27 ]. These interventions, as highlighted by participants, directly link resilience to the welfare of children, further underlining the importance of supporting the non-AUD husband in their parenting role [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Self-care is crucial for maintaining mental and physical health, and previous research has emphasized its role in promoting emotional well-being. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%